2018
DOI: 10.1002/joc.5951
|View full text |Cite
|
Sign up to set email alerts
|

How does temporal trend of reference evapotranspiration over the Tibetan Plateau change with elevation?

Abstract: Considerable efforts have been made to determine spatial and temporal patterns and the driving factors for reference evapotranspiration (RET) over the Tibetan Plateau (TP). Yet, how temporal trends of RET vary with respect to elevation is less clear. By using long-term daily meteorological records of 84 stations from 1971 to 2015, this study investigates the elevation dependence of RET trend over the TP. The results show that both increasing and decreasing trends of RET for the study period exist over the TP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…All of them have caused the rapid wetter condition at highland regions. Together with global warming that glaciers in the QTP rapidly shrinks 43 , more streamflow was yielded in the region 25 . We concluded that the surrounding areas easily suffered from meteorological drought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them have caused the rapid wetter condition at highland regions. Together with global warming that glaciers in the QTP rapidly shrinks 43 , more streamflow was yielded in the region 25 . We concluded that the surrounding areas easily suffered from meteorological drought.…”
Section: Discussionmentioning
confidence: 99%
“…The Hurst index is used to predict the persistence of the time series. It can be computed by the method of rescaled range analysis (R/S) 25,26 . The following are the calculation steps:…”
Section: Methods Standardized Precipitation Evapotranspiration Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The WS dominated the decrease in ET 0 at low elevations, while T dominated increasing ET 0 at high elevations. Zhang et al [46] found that increasing (decreasing) trends in ET 0 over the Tibetan Plateau and overall were negatively (positively) related to rising elevation over their study period , with the absolute trends in ET 0 becoming smaller along with rising elevation. Although there is growing evidence that the rate of warming is amplified with elevation, known as 'elevation-dependent warming' [47], especially in the Tibetan Plateau [25], elevation-dependent warming was insignificant in NWC; the relative contribution of warming to ET 0 variation was correlated to elevation (Figure 10).…”
Section: Effect Of Elevation On the Variation Of Etmentioning
confidence: 85%
“…The conditions of the reference evapotranspiration are unlikely to be met across large areas in some regions, such as the Tibetan Plateau (e.g. Zhang, Wang, & Chen, 2019), However, as was claimed by Allen et al (1998), the Penman-Monteith approach for estimating reference evapotranspiration does not fuel controversy and provides consistent and reliable information in different weather conditions and locations, which is why it is recommended by the Food and Agriculture Organization of the United Nations. Although the Penman-Monteith equation is more often recommended (Beguería et al, 2014) to estimate PET in the computation of SPEI, whether the Thornthwaite approach or Penman-Monteith equation is employed, similar estimates of PDSI seem to be produced (van der Schrier et al, 2011).…”
Section: Dominant Modes Of Variability Of Drought Indicesmentioning
confidence: 99%